Liver graft preservation using perfluorocarbon improves the outcomes of simulated donation after cardiac death liver transplantation in rats. Issue 9 (September 2017) - Okumura, Shinya; Uemura, Tadahiro; Zhao, Xiangdong; Masano, Yuki; Tsuruyama, Tatsuaki; Fujimoto, Yasuhiro; Iida, Taku; Yagi, Shintaro; Bezinover, Dmitri; Spiess, Bruce; Kaido, Toshimi; Uemoto, Shinji
Abstract : The outcomes of liver transplantation (LT) from donation after cardiac death (DCD) donors remain poor due to severe warm ischemia injury. Perfluorocarbon (PFC) is a novel compound with high oxygen carrying capacity. In the present study, a rat model simulating DCD LT was used, and the impact of improved graft oxygenation provided by PFC addition on liver ischemia/reperfusion injury (IRI) and survival after DCD LT was investigated. Orthotopic liver transplants were performed in male Lewis rats, using DCD liver grafts preserved with cold University of Wisconsin (UW) solution in the control group and preserved with cold oxygenated UW solution with addition of 20% PFC in the PFC group. For experiment I, in a 30‐minute donor warm ischemia model, postoperative graft injury was analyzed at 3 and 6 hours after transplantation. For experiment II, in a 50‐minute donor warm ischemia model, the postoperative survival was assessed. For experiment I, the levels of serum aspartate aminotransferase, alanine aminotransferase, hyaluronic acid, malondialdehyde, and several inflammatory cytokines were significantly lower in the PFC group. The hepatic expression levels of tumor necrosis factor α and interleukin 6 were significantly lower, and the expression level of heme oxygenase 1 was significantly higher in the PFC group. Histological analysis showed significantly less necrosis and apoptosis in the PFC group. Sinusoidal endothelial cells and microvilli of the bile canaliculi were well preserved in the PFC group. For experiment II, the postoperative survival rate was significantly improved in the PFC group. In conclusion, graft preservation with PFC attenuated liver IRI and improved postoperative survival. This graft preservation protocol might be a new therapeutic option to improve the outcomes of DCD LT. Liver Transplantation 23 1171–1185 2017 AASLD.